2011
DOI: 10.1089/aid.2010.0237
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of CD1d-Restricted Natural Killer T Cells in Chronic HIV Type 1 Clade C Infection

Abstract: Recent studies suggest that natural killer T (NKT) cells play a role in early antiviral pathogenesis and are rapidly depleted in chronic human immunodeficiency virus type 1 (HIV-1) clade B infection. We aimed to characterize the phenotypic and functional characteristics of NKT cells in HIV-1 clade C-infected Africans at different stages of HIV-1 disease. NKT cell frequencies, subsets, and ex vivo effector functions were assessed using multiparametric flow cytometry in a cross-sectional analysis of cryopreserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…However, much more must be known about the specificity of the natural killer cell receptors, particularly those used by the activating killer immunoglobulin-like receptors, before such vaccines can be designed. Also the possibility of modulating natural killer T cells 62 and regulatory T cells 63,64 , diminishing loss of the T H 17 subset of helper T cells in the gut 65 and decreasing T cell activation 66 during acute infection with HIV-1 could be worth exploring further.…”
Section: Vaccines That Induce T Cell Responsesmentioning
confidence: 99%
“…However, much more must be known about the specificity of the natural killer cell receptors, particularly those used by the activating killer immunoglobulin-like receptors, before such vaccines can be designed. Also the possibility of modulating natural killer T cells 62 and regulatory T cells 63,64 , diminishing loss of the T H 17 subset of helper T cells in the gut 65 and decreasing T cell activation 66 during acute infection with HIV-1 could be worth exploring further.…”
Section: Vaccines That Induce T Cell Responsesmentioning
confidence: 99%
“…To determine the impact of iNKT LAG-3 expression, we assessed functional iNKT cytokine production capacity in the Majengo cohort. Studies of iNKT function during HIV infection and treatment in the literature suffer from lack of replication in multiple cohorts, and the only functional study performed in an African cohort reported only PMA/Io-stimulated cytokine production from ART-naïve subjects [ 33 ]. The decrease in αGalCer-induced IFNγ expression is similar to other cohorts, but the lack of functional reconstitution among ART experienced participants in this cohort is concerning [ 30 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These strategies comprise depletion and functional impairment of iNKT cells and interference with CD1d expression in APCs. In HIV-1-infected individuals, the iNKT cell compartment in peripheral blood is severely depleted [1416], and even if some patients suffer from only a minimal depletion, their iNKT cells display an exhausted phenotype characterized by elevated programmed cell death protein 1 expression and reduced responsiveness to α-GalCer stimulation [1719]. Interestingly, similar observations have been made in macaques infected with simian immunodeficiency virus, the precursor of HIV-1 [20].…”
Section: Introductionmentioning
confidence: 92%